A knowledge hierarchy in labour and welfare services? Evidence‐based and practice‐based knowledge in frontline service innovation. (30th October 2018) - Breit, Eric; Fossestøl, Knut; Pedersen, Eirin
Abstract: Although policy‐makers and scholars have directed increasing attention towards collaborative innovation and knowledge development between frontline agencies and workers and other stakeholders such as citizens and researchers, empirical research has not focused on the (varying) assessment of collaborators regarding what knowledge is "appropriate" to develop. In this article, we examine such knowledge assessments by drawing on a comparative case study of two local innovation projects conducted by the Norwegian Labour and Welfare Administration (NAV) in a four‐year service innovation programme. Although they responded to the same call, the projects involved development of two very distinct types of knowledge; one dealt with practice‐based knowledge and the other with evidence‐based knowledge. We show that whereas the former knowledge type was contested and difficult to transform into practice, the latter prompted few (if any) challenges and was implemented on a relatively large scale. These two projects point to the possible existence of a hierarchy of knowledge in labour and welfare services, where evidence‐based forms of knowledge and methods are regarded as more legitimate and appropriate than forms of knowledge placed "lower" in the hierarchy. We discuss the reasons for and implications of this apparent hierarchy of knowledge for frontline labour and welfare services.